Morbidity patterns amongst hospitalized children in a secondary care hospital of Uttarakhand, India - Tyagi, Brij Bhushan; S., Haroon A.; Negi, Vijay Kumar; Bhardwaj, Narendra Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Life expectancy at birth, mortality and morbidity rates are important indicators of health status of a population. This study aimed at providing statistical data related to the morbidity patterns of common illnesses seen in children admitted to a secondary care, state run hospital. Methods:The study population comprised of children in the age group of 0 to 14 years, admitted during the year 2012 (from 1st January to 31st December 2012). A retrospective record analysis was carried out from the data available in the medical records department. Results: During the study period, the total numbers of admissions were 3389. Nearly 39.80% (n=1349) were girl and 60.20% (n=2040) were boys with a sex ratio of 661 girls to 1000 boys. The median age for boys was 6.1 years, girls 6.5 years and for both 6.3 years and had statistical significance (11.40 (P<0.05)) at 5 percent level. Study shows that significant gender inequality was observed in morbidity prevalence in girls compared to boys. Case fatality rate (CFR) among boy infants (2.42%) was higher than girls in all age groups. The bed occupancy rate (BOR) was recorded at 135.3 per cent throughout the year. Neonates admitted were all referral cases. Conclusions:The study highlights that three fourth of the hospitalized children were suffering from morbidity events like bacterial infection and acute respiratory problems. More care and attention needs to be paid in children of younger age group.